Soil Characteristics Under Sago Stands (Metroxylon sp) Under Different Inundation Conditions in Rupaitu Negeri Tulehu Hamlet, Salahutu District, Central Maluku Regency - Ampi O Tumewu; Marcus Luhukay; Anjelin Elly (Universitas Pattimura, 2023)
s study aims to identify the characteristics of the soil that develops on sago land with different inundation conditions and determine the type of soil on sago land with different inundation conditions. The method used is survey method. Determination of the observation points of the soil profile at the study site was based on inundation conditions obtained through interviews with sago processing farmers at the study site. Soil characteristics on permanently flooded land are dominated by the color of glei wAhich has undergone a reduction process. On land with periodic inundation conditions that undergo an oxidation-reduction process is dominated by motling colors and in non-flooded conditions no glei or motling colors are found. In conditions of permanent inundation and periodic inundation, no identifying horizon has been found except in non-flooded conditions, a cambic (Bw) identifying horizon has been found. The dominant soil formation factors are climate (rainfall) and topography. Rainfall and topography affect the depth of groundwater and inundation. The soil formation process that occurs is the gleization process in Gleisol soils and the leaching process occurs in Kambisol soils. Differences in soil types due to differences in inundation conditions are not yet clear, but the differences in soil types are clear, namely Gleisol hydrik (Typic hydraquents), Gleisol district (Typic epiaquepts) and Gleisol fluvik (Fluvaquentic epiaquepts) and Cambisol oxic (Typic dsytrudepts).